System physiology of respiratory control in man - Tadayoshi Miyamoto (Japanese Society of Physical Fitness and Sports Medicine, 2016)
The respiratory control system is an important chemoreflex-feedback control system that maintains arterial partial pressures of CO2 (PaCO2), O2 and pH remarkably constant via ventilatory regulation. It can be divided into two subsystems: a controller (controlling element) and a plant (controlled element). The respiratory operating point (ventilatory or PaCO2 response) is determined by the interplay between the controller (arterial PCO2 [PaCO2] → minute ventilation [VE] relation) and plant (VE → PaCO2 relation) subsystem elements within the respiratory control system. This review outlines the methodology of converting the closed loop of the respiratory control system to an open loop state, then simplifying the controller and plant subsystems, and identifying the input−output relationship using a systems physiological technique (equilibrium diagram method). Changes in central hemodynamics, exercise stimulus, and regular exercise training modify VE and/or PaCO2 levels at rest and during exercise. These respiratory changes can be quantitatively explained by changes in two subsystem elements on the respiratory equilibrium diagram. Using this analysis technique that allows an integrated and quantitative description of the whole respiratory control system will greatly advance the elucidation of pathological conditions manifesting breathing disorders and respiratory regulation during exercise. By repeating thought experiments utilizing this kind of mathematic model and physiological experiments that provide evidence, deeper understanding will be achieved concerning prediction of the behavior of biological systems beyond the physiological range and understanding of the pathophysiology of diseases that are difficult to study by clinical research.